Resistência e reprodução camponesa em áreas de reforma agrária no Curimataú Oriental da Paraíba: o caso do assentamento Sitio - Silva, José de Arimateia de Oliveira (2021)
This research has as its main focus, understanding the different forms of resistance it's from peasant reproduction present in the third oldest Settlement Project created in the geographical micro-region of Curimataú Oriental da Paraíba, the PA Site, located in the municipality of Dona Inês seeking to verify to what extent it fits into the perspective of what Moreira (2006; 2018) calls the “Hope Territory”. For its realization, secondary data that had IBGE and INCRA as sources were used. The primary data were collected in the field work. This one, which started in 2019, had to be stopped due to the pandemic during almost the entire year of 2020, being resumed at different times when the settlers consented to receive us. Eight interviews were conducted with structured and semi-structured scripts with settled peasants, family heads responsible for the lots or their representatives, in addition to the STR leaders, of the Association of Workers of the PA Site, between others. Twenty-one questionnaires were also applied to settled peasants responsible for the family unit (heads of the family), which represents approximately 30% of the total number of heads of households settled in the PA. The survey found that the peasantry settled in the PA Site uses different strategies of resistance and recreation, as well as adopting various forms of struggle for permanence on earth denying, therefore, the theory of its destruction in the capitalist mode of production.